AfricaRice innovations contribute to the rice production and value chain upgrading with 10,890 producers in West Africa benefited from contract farming - CGIAR Research Program on Rice (2020)
We assess the state of rice value chain upgrading in West Africa by reviewing evidence on rice millers’ investment in semi-industrial and industrial milling technologies, contract farming and vertical integration during 2009–2019. We found that upgrading is more dynamic in countries with high production and import bills. In 2019, there were 57 industrial mills with an aggregate capacity of 315 tons/hour. We found contract farming in eight countries, involving 10,890 producers, and vertical coordination in five countries, covering 29,240 ha.